Healing in a cultural context: the role of healing as a defining character in the growth and popular faith of the Zion Christian Church - Mashabela, James K. (Studia historiae ecclesiasticae, 2017)
This article revisits the role healing has played in the growth of the Zion Christian Church (ZCC) as one of the fastest growing African Independent Churches (AICs) in South Africa. The article argues that the ZCC is appealing to black Africans because it addresses healing within the cultural context of an African. Healing within the cultural context speaks to the fundamental needs of an African. The fundamental needs of an African see healing as addressing more than just a body ailment, but the totality of a person. The paper revisits the history of healing in the ZCC, and in so doing, will be a revisit to this church's history. In revisiting this history, the discrimination that this church faced from the political authorities and from the white mission churches will also be referred to.
free
Keywords: Africa.; Baptism – African independent churches; Christianity and African religions; Christianity and culture; Colonialism and neocolonialism; Healing; Spiritual; Health and religion; Lekganyane; Engenas; 1885?-1948; Medicine – Philosophy; Theology; Water – Religious aspects – Christianity; Zion Christian Church